Warming alters coupled carbon and nutrient cycles in experimental streams. (8th March 2016) - Williamson, Tanner J.; Cross, Wyatt F.; Benstead, Jonathan P.; Gíslason, Gísli M.; Hood, James M.; Huryn, Alexander D.; Johnson, Philip W.; Welter, Jill R.
Abstract: Although much effort has been devoted to quantifying how warming alters carbon cycling across diverse ecosystems, less is known about how these changes are linked to the cycling of bioavailable nitrogen and phosphorus. In freshwater ecosystems, benthic biofilms (i.e. thin films of algae, bacteria, fungi, and detrital matter) act as biogeochemical hotspots by controlling important fluxes of energy and material. Understanding how biofilms respond to warming is thus critical for predicting responses of coupled elemental cycles in freshwater systems. We developed biofilm communities in experimental streamside channels along a gradient of mean water temperatures (7.5–23.6 °C), while closely maintaining natural diel and seasonal temperature variation with a common water and propagule source. Both structural (i.e. biomass, stoichiometry, assemblage structure) and functional (i.e. metabolism, N2 ‐fixation, nutrient uptake) attributes of biofilms were measured on multiple dates to link changes in carbon flow explicitly to the dynamics of nitrogen and phosphorus. Temperature had strong positive effects on biofilm biomass (2.8‐ to 24‐fold variation) and net ecosystem productivity (44‐ to 317‐fold variation), despite extremely low concentrations of limiting dissolved nitrogen. Temperature had surprisingly minimal effects on biofilm stoichiometry: carbon:nitrogen (C:N) ratios were temperature‐invariant, while carbon:phosphorus (C:P) ratios declined slightly with increasing temperature. Biofilm communities were dominated by cyanobacteria at all temperatures (>91% of total biovolume) and N2 ‐fixation rates increased up to 120‐fold between the coldest and warmest treatments. Although ammonium‐N uptake increased with temperature (2.8‐ to 6.8‐fold variation), the much higher N2 ‐fixation rates supplied the majority of N to the ecosystem at higher temperatures. Our results demonstrate that temperature can alter how carbon is cycled and coupled to nitrogen and phosphorus. The uncoupling of C fixation from dissolved inorganic nitrogen supply produced large unexpected changes in biofilm development, elemental cycling, and likely downstream exports of nutrients and organic matter.